Toughening epoxy syntactic foams with milled carbon fibres: Mechanical properties and toughening mechanisms - He,S; Carolan,D; Fergusson,A; Taylor,AC (2019)
Syntactic foams comprising hollow glass microspheres (GMS) in an epoxy matrix are critical for lightweight structures, being extensively used in marine and aerospace as cores for composite sandwich panels. They are buoyant and crush resistant, but their use is limited by their brittleness. Milled carbon fibres (MCF) were used to increase toughness, by introducing energy absorption mechanisms, to foams comprising ∼60 vol% GMS. Weight ratios of up to 40% MCF:GMS were used. The tensile modulus of the foams increased from 3.36 GPa to 5.41 GPa with the addition of 40% weight ratio of MCF. The tensile strength of the syntactic foam decreased then increase when more MCF particles are added, and the mechanisms responsible are explained for the first time. The fracture energy of the syntactic foam increased by 183%, from 182 J/m2 to 516 J/m2, due to the addition of 40% weight ratio of MCF. Toughening mechanisms were identified as crack deflection, debonding and subsequent plastic void growth, and fibre pull-out. Thus, the simple and cheap addition of MCF greatly increases the toughness of the syntactic foams, enabling lighter or more damage-resistant structures.